Analysis of cost structure of international road transport operators in West Pomeranian voivodship in the years 2008-2014 - Błazėj Supron\' (The Central European Review of Economics and Management (CEREM), 2018)
Aim: The analysis of the cost structure and the factors determining these costs constitutes an important subject that is applied for both strategic planning of the company's activity and the evaluation of the actions taken before. The aim of the study was to analyze the structure of the costs incurred by transport enterprises operating in the territory of West Pomeranian Voivodeship in the period from 2008 to 2014, as well as the factors which determined cost variations.Design / Research methods: Literature research provided an introduction to the discussion along with an analysis of the secondary sources concerned with the subject of the study. Achieving the goals required the analysis of financial reports compiled by the enterprises examined for 2008-2014. The methods of descriptive statistics were used for collecting the data. Considering the fact that the study included more than half of the target group the results obtained can be referred with considerable caution to all other economic operators of this kind in the West Pomeranian Voivodeship.Conclusions / findings: The results found that the costs of the enterprises examined were to the largest extent influenced by macroeconomic factors, such as interest rates, fuel prices, as well as the situation on the job market. Micro-enterprises were the most vulnerable to the changes in these factors. The study showed that there is a significant correlation between the expenses borne and the economic situation on the EU market.Originality / value of the article:~ While the majority of the compilations concerning transport enterprises focuses on their general situation, the results of this study provide a thorough analysis of the internal situation of the entities examined and indicate the influence of the individual factors on the market situation of these entities. It is the first compilation focusing on transport enterprises which undertakes the analysis of the costs they incur applying such a broad aspect.Implications of the research (if applicable): The results may be used by individuals who manage transport enterprises in order to track, within the framework of an ex post analysis, the factors influencing the costs, as well as their future optimization. From the scientific perspective, the findings may be applied for further considerations concerning the road transport sector and its market situation.Limitations of the research: The main limitation of the study is the incomplete picture of the situation of all transport enterprises in West Pomeranian Voivodeship. Due to the lack of comparability of the financial data, as well as the difficulties in obtaining them, the study did not include the companies which are not required to publish financial reports and those keeping tax records. Another limitation is the lack of the data on enterprises which~ did not submit their reports to the relevant registers despite being obligated to do so.Key words: costs, transport enterprises, cost structureJEL: R41~
Keywords: R41; 330; costs; transport enterprises; cost structure